INDUCED ABORTION AS PĀṆĀTIPĀTA: Revisiting Buddhist Position on the Right to Life of an Unborn - Anand, Abhinav (Journal of Dharma, 2020)
In this paper, investigating the issue whether Buddhism proposes (a) pro-life, (b) pro-choice, (c) middle way, or (d) ambiguous position on the issues of abortion, three questions are examined: (i) when does an individual life begin according to the early Buddhist texts? (ii) what are the cases of abortion recorded in the Pāli texts? (iii) how and why the Buddhist metaphysical and ethical principles prohibits killing? Analysing selected passages of Pāli texts such as Majjhima, Saṃyutta and Aṇguttara Nikāya-s, Vinaya Piṭaka, Milindapañha, Dhammapada and Jātaka, and their metaphysical and ethical ideas the author argues that abortion is an act of pāṇātipāta (killing) a moral being and is prohibited.